2004
DOI: 10.1002/hup.585
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization review of risperidone for outpatients in a tertiary referral hospital in Singapore

Abstract: The mean risperidone dose during the study period was towards the lower end of recommendation for schizophrenia. Further study is warranted to confirm and explain the pattern of low-dose risperidone, and the high use of concomitant conventional antipsychotics and anti-Parkinsonian agents in Singapore. Elucidation of these would provide a valuable insight for the management of Asian patients with schizophrenia using risperidone. However, the current data indicate that the practice of using a lower dose of rispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
0
1
Order By: Relevance
“…SGAs are generally considered to have lower risk of EPS than FGAs; however, in the case of risperidone, both Luo et al 32 and our study did not find a lower EPS risk. Furthermore, we found that not all SGAs have a similar risk.…”
Section: Discussioncontrasting
confidence: 85%
“…SGAs are generally considered to have lower risk of EPS than FGAs; however, in the case of risperidone, both Luo et al 32 and our study did not find a lower EPS risk. Furthermore, we found that not all SGAs have a similar risk.…”
Section: Discussioncontrasting
confidence: 85%